Differential Diagnosis between Ulcerative Colitis and Clostridium Difficile-Associated Disease in a Patient with Autoimmune Polyglandular Syndrome Type 1 - Elizaveta A. Trush; Alexander V. Korolev; Elena A. Poluektova; Pavel V. Pavlov; Maria G. Pavlova; Alexander S. Tertychny; Yulia O. Sidorina; Natalia A. Ponkratova; Oleg S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to demonstrate the clinical picture and the tactics of differential diagnosis between ulcerative colitis and Clostridium difficile-associated disease in a patient with APS-1, as well as to describe the tactics of managing such patients.Key findings. A 25-year-old patient with autoimmune polyglandular syndrome type 1 (APS-1) complained of loose stools up to 10 times a day with blood admixture, rapidly growing weakness and a weight loss of 5 kg per week. When examined on the day of admission, surgical pathology was excluded. Further differential diagnostics between Clostridium difficile-associated disease and ulcerative colitis was carried out, with the possibility of combining these diseases being not excluded. The examination confirmed Clostridium difficile-associated disease, while the diagnosis of ulcerative colitis needed further verification. APS-1 is often combined with other diseases and is likely to be pathogenetically related with them; however, the mechanisms of such interrelations still remain unknown. Previous research has reported the relationship between APS-1 and clostridial infection. The combination of ulcerative colitis with APS-1 has not thus far been described.Conclusion. A specific feature of the described clinical case consists in the development of severe Clostridium difficile-associated disease against the background of autoimmune polyglandular syndrome type 1. The management of patients with APS-1 should take into account the possibility of developing a clostridial infection, since these diseases can co-occur. When treating a patient with APS-1 in non-endocrine hospital units, consultation with an endocrinologist is necessary.